2015
DOI: 10.1111/ecc.12290
|View full text |Cite
|
Sign up to set email alerts
|

Psychological effects of a cosmetic education programme in patients with breast cancer

Abstract: Treatments for breast cancer often include interventions related to psychosocial issues such as negative body image, loss of femininity, and low self-esteem. We identified the psychological effects of a cosmetics education programme in patients with breast cancer. Cosmetic programme is a specific care designed to help patients handle appearance-related side effects. Thirty-one women with breast cancer at a university hospital in South Korea who received a cosmetics education programme were compared with 29 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
47
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(52 citation statements)
references
References 65 publications
3
47
1
1
Order By: Relevance
“…Contrary to our expectation, the current intervention had no differential effect on body image as both groups reported similar increases over time. While these results indeed were in line with one recent study, positive effects on body image have been documented previously in breast cancer patients receiving a beauty care intervention within 1‐week postsurgery, pointing towards the need for interventions to be carried out close to the onset of cancer treatment to have an effect on body image satisfaction as well. Thus, body image effects of the current intervention may be attenuated by the longer duration between diagnosis and intervention.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Contrary to our expectation, the current intervention had no differential effect on body image as both groups reported similar increases over time. While these results indeed were in line with one recent study, positive effects on body image have been documented previously in breast cancer patients receiving a beauty care intervention within 1‐week postsurgery, pointing towards the need for interventions to be carried out close to the onset of cancer treatment to have an effect on body image satisfaction as well. Thus, body image effects of the current intervention may be attenuated by the longer duration between diagnosis and intervention.…”
Section: Discussionsupporting
confidence: 90%
“…However, it has been less clear whether these interventions only have a short‐term or also a longer‐term psychological effect, as prior results were often limited to treatment effects, which were investigated immediately after the intervention (eg, on the same day) or to studies that did not implement a randomized control group design. In contrast to previous studies (eg,), the current study was the first to consistently demonstrate midterm improvements on a range of psychological outcomes. As previous studies varied to a large degree regarding the examined follow‐up intervals, this may be due to methodological differences: Some studies did not include follow‐up assessments, thus leaving it unclear if the intervention had any lasting effect at all; others used quite long follow‐up intervals (eg, several months) with no in‐between measurement points and indicated no lasting treatment effect.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Park et al . () found that women were less likely to experience distress having gone through the programme, potentially serving as a diversion from illness and improving mood. This study demonstrates how professionals can run simple well‐being programmes, perhaps in the future with a greater focus on positive coping strategies and self‐esteem.…”
mentioning
confidence: 99%
“…A study from Korea by Park et al . () highlights how a cosmetics educational programme in patients with breast cancer may help patients better handle appearance‐related side effects. Based on the initiatives such as ‘Look good, feel better’ (http://www.lookgoodfeelbetter.co.uk) in the UK, this programme aimed to enhance body image through a makeup and wig workshop.…”
mentioning
confidence: 99%